Robotic Bartender Control Using DC and Servo Motor with The Aid of Rectifier as Power Source - Mohd Noor, Muhammad Haziq; Jenal, Mahyuzie; Khairul Anwar Ibrahim (Emerging Advances in Integrated Technology, 2024)
The project builds a design and implement of robotic bartender prototype using rectifier as power source embedded with digital voltammeter display to monitor supply voltage and current of load used. The usage of robotic bartender in the market make ease to the worker staff in food and beverage industries so that they can prepare drinks to customer in short amount of time. For this paper, the design of robotic bartender is implement using 3D printed components and use Arduino UNO as microcontroller to control input signal of rotary encoder and switches to commodore DC motor rotation and servo motor deflection. The prototype of robotic bartender will be constructed, programmed with C language, circuit tested with Proteus simulation software and hardware will be tested by using tachometer laboratory equipment for speed testing. Lastly the overall system is powered by rectifier with embedded digital voltammeter display for convenient use.